The Versatility of the Roskamp Homologation in Synthesis - Margherita Miele; Aljoša Smajić; Vittorio Pace (Molecules)
Modern organic synthesis continues to benefit from the flexibility of α-diazo carbonyl intermediates. In the context of homologation processes, the Roskamp reaction—first introduced in 1989—has become a valuable tool due to its selectivity and mild condition reactions for accessing important synthons amenable to further functionalization as β-keto esters. The fine-tuning of reaction parameters—including the nature of Lewis acids, solvents, and temperature—has enabled the development of catalyzed continuous-flow methodologies, as well as a series of asymmetric variants characterized by high transformation rates, excellent stereocontrol, and formidable chemoselectivity. This review aims to emphasize the attractive features of the Roskamp reaction and its applicability for addressing challenging homologation processes.